Keberlakuan Pemberian Uang Panjar Berdasarkan Hukum Adat Analisis Perjanjian Jual Beli Tanah Yang Dapat Membatalkan Perjanjian Pengikatan Jual Beli Dan Surat Kuasa Menjual Yang Dibuat Oleh Notaris - Herina; Mohammad Ryan Bakry; Chandra Yusuf (JOSH: Journal of Sharia, 2024)
Applicability of giving down payment based on customary law: analysis of land sale and purchase agreements that can cancel binding sale and purchase agreements and power of attorney to sell made by a notary. The payment system is known as down payment or receipt money. Buying and selling with a down payment system is a sale and purchase that is usually carried out in the community. By way of the buyer providing part of the payment as collateral or binding the transaction, and setting a deadline to pay off the remaining price. The purpose of this study is to examine more deeply the provision of down payment as a token of appreciation in land sale and purchase agreements based on customary law in Indonesia. To analyze whether or not a land sale and purchase agreement is valid orally and has been given a down payment as a sign of completion. The type of research used in this research is normative juridical research method. The normative juridical approach is a problem approach by viewing, analyzing and interpreting theoretical matters relating to legal principles in the form of conceptions, norms, rules of laws and regulations, court decisions, agreements and doctrines (teachings). The legal moral position of down payment is useful as the main benchmark in agreements made by customary law communities related to goodwill. This is appropriate that in customary law goodwill and halal clauses are the main and foremost things. Because morality is very closely related to law, where a good law is a law based on morality, so that a law has a spirit, both from the product of the law and the spirit of law enforcers, so that the law can be upheld in order to obtain justice, legal certainty and expediency. The law provides a limit on how morals can be carried out with various law enforcement efforts, not just with threats/sanctions for violators.